Well-Being in the Workplace A Guide to Resilience for Individuals and Teams. - Cook, Sarah (IT Governance Ltd, 2021)
Well-being in the Workplace - A guide to resilience for individuals and teams is aimed at managers who need to build resilience in both themselves and their team and improve their own and others' well-being. Managers, team leaders, those in HR roles, and employees looking to adapt to new ways of working will find this book invaluable.
Description based upon print version of record.
Keywords: Resilience (Personality trait); Well-being.; Human comfort.; elektronické knihy; electronic books